Varicella and Fournier′s gangrene - Arcot Rekha; Annamalai Ravi (Wolters Kluwer Medknow Publications, 2007)
Fournier′s gangrene is the necrotizing fasciitis of the scrotum and the perineum. The treatment involves early recognition, aggressive resuscitation, radical debridement and appropriate antibiotics. Even though its association with varicella is known to occur in children, it is found to be uncommon in adults. We present our findings and review literature regarding the associations, clinical presentations and management of Fournier′s gangrene.